1977
DOI: 10.1083/jcb.75.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Calcium content and distribution as a function of growth and transformation in the mouse 3T3 cell

Abstract: Total Ca content and that fraction of Ca sensitive to removal by the chelator ethylene glycol-bis(/~-aminoethyl ether) N,N,N',N'-tetraacetate (EGTA) have been investigated in the mouse 3T3 cell as a function of growth stage, transformation with SV40 virus, and serum levels of the media. Cells were allowed to grow through several doublings in media containing 45Ca. The cellular content of 45Ca was used to assess total cell Ca. That fraction of 45Ca removed by EGTA was presumed to represent primarily surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…In preliminary experiments a range of different washing regimens were examined for cells exposed to radio-calcium. These showed a near exponen tial decrease in cell-associated calcium when cultures were washed successively with 0.9% saline and that in some cases up to ten washes were necessary to reach a basal level of radioactivity in the washes which is in agreement with previous findings (3,6). Approxima tely 96% of the residual cell-associated calcium was removed by 3 subsequent 0.1 M lanthanum chloride washes, 89% by washing the cultures with EGTA (2.5 mM at pH 7.2) and 78% by trypsinising the cells.…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…In preliminary experiments a range of different washing regimens were examined for cells exposed to radio-calcium. These showed a near exponen tial decrease in cell-associated calcium when cultures were washed successively with 0.9% saline and that in some cases up to ten washes were necessary to reach a basal level of radioactivity in the washes which is in agreement with previous findings (3,6). Approxima tely 96% of the residual cell-associated calcium was removed by 3 subsequent 0.1 M lanthanum chloride washes, 89% by washing the cultures with EGTA (2.5 mM at pH 7.2) and 78% by trypsinising the cells.…”
Section: Methodssupporting
confidence: 82%
“…Approxima tely 96% of the residual cell-associated calcium was removed by 3 subsequent 0.1 M lanthanum chloride washes, 89% by washing the cultures with EGTA (2.5 mM at pH 7.2) and 78% by trypsinising the cells. These results imply that a significant proportion of the cell-associated calcium is external as has been previously demonstrated (3,4,6). The washing schedule that was finally employed in the present study consisted of two saline washes in which the wells were rinsed in a stream of 0.9% saline, allowed to stand in 1 ml/well of saline for 10 min, rinsed again and given a second wash (1 ml/well) for 3 -5 min.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…shown to be substantially lower than that of nontransformed cells (10). It has also been shown that addition ofinsulin to chicken embryo cells or of fresh medium to 3T3 cells releases more -than half the surface-bound Ca2+ of these cells into the medium (11,12).…”
Section: Methodsmentioning
confidence: 98%
“…EDTA has been shown (24) to rapidly remove (half-life, 1.5 min) cell surface Ca2+ from HeLa cells, whereas a second larger pool, presumed to be cytoplasmic Ca2+, is removed by EDTA much more slowly (half-life, 31 min). Because chelating agents have been shown to have similar effects on the Ca2+ content of 3T3 cells (25), addition of 10 mM EDTA to the culture medium (which contains 1.8 mM CaCl2) would be expected to inhibit primarily cell surface PLase.…”
Section: Pge2mentioning
confidence: 99%